Pengaruh Tekanan Keuangan Dan Kapitalisasi Pasar Terhadap Nilai Pasar Perusahaan Transportasi Di Indonesia - Deni Sunaryo; Abdul Fatah; Abdul Malik (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Objective This study aims to determine the Effect of Financial Pressure and Market Capitalization on the Market Value of Companies in the transportation. The population used in this study is the transportation sub-sector companies listed on the Indonesia Stock Exchange (BEI) from 2013 to 2018. The sampling technique used was purposive sampling method and obtained 10 companies. The data collected is secondary data with the documentation method through www. .idx.com is the company's annual report. The analytical tool used to test hypotheses is SPSS23. The results of this study are (1) Financial Pressure has a significant effect on the Company's Market Value, (2) Market Capitalization has no effect on the Company's Market Value